Biomaterials in prosthodontics: current trends and future directions - Raghavan, Rohit; P. A., Shajahan; S., Shalu (International Journal of Research in Medical Sciences, 2026)
Alqutaibi AY, Baik A, Almuzaini SA, Farghal AE, Alnazzawi AA, Borzangy S, et al. Polymeric denture base materials: a review. Polymers (Basel). 2023;15(15):3258. Pjetursson BE, Sailer I, Makarov NA, Zwahlen M, Thoma DS. All-ceramic or metal-ceramic tooth-supported fixed dental prostheses (FDPs)? A systematic review of the survival and complication rates. Part II: multiple-unit FDPs. Dent Mater. 2015;31(6):624-39. Osman RB, Swain MV. A critical review of dental implant materials with an emphasis on titanium versus zirconia. Materials (Basel). 2015;8(3):932-58. Rezaie F, Farshbaf M, Dahri M, Masjedi M, Maleki R, Amini F, et al. 3D printing of dental prostheses: current and emerging applications. J Compos Sci. 2023;7(2):80. Alghazzawi TF. Advancements in CAD/CAM technology: options for practical implementation. J Prosthodont Res. 2016;60(2):72-84. Javaid M, Haleem A. Current status and applications of additive manufacturing in dentistry: a literature-based review. J Oral Biol Craniofac Res. 2019;9(3):179-85. Vallittu PK, Boccaccini AR, Hupa L, Watts DC. Bioactive dental materials—do they exist and what does bioactivity mean? Dent Mater. 2018;34(5):693-4. Sun J, Jiang J, Huang Z, Ma X, Shen T, Pan J, et al. Smart biomaterials in restorative dentistry: recent advances and future perspectives. Mater Today Bio. 2025;35:102349. Revilla-León M, Özcan M. Additive manufacturing technologies used for processing polymers: current status and potential application in prosthetic dentistry. J Prosthodont. 2019;28(2):146-58. Najeeb S, Zafar MS, Khurshid Z, Siddiqui F. Applications of polyetheretherketone (PEEK) in oral implantology and prosthodontics. J Prosthodont Res. 2016;60(1):12-9. Albrektsson T, Wennerberg A. Oral implant surfaces: part 2—review focusing on clinical knowledge of different surfaces. Int J Prosthodont. 2004;17(5):544-64. Tappa K, Jammalamadaka U. Novel biomaterials used in medical 3D printing techniques. J Funct Biomater. 2018;9(1):17. Liu Y, Fang M, Zhao R, Liu H, Li K, Tian M, et al. Clinical applications of polyetheretherketone in removable dental prostheses: accuracy, characteristics, and performance. Polymers (Basel). 2022;14(21):4615. Chander NG, Gopi A. Trends and future perspectives of 3D printing in prosthodontics. Med J Armed Forces India. 2024;80(4):399-403. Hench LL, Jones JR. Bioactive glasses: frontiers and challenges. Front Bioeng Biotechnol. 2015;3:194. Albrektsson T, Brånemark PI, Hansson HA, Lindström J. Osseointegrated titanium implants: requirements for ensuring a long-lasting, direct bone-to-implant anchorage in man. Acta Orthop Scand. 1981;52(2):155-70. Goodacre CJ, Bernal G, Rungcharassaeng K, Kan JYK. Clinical complications with implants and implant prostheses. J Prosthet Dent. 2003;90(2):121-32. Padhye NM, Calciolari E, Zuercher AN, Tagliaferri S, Donos N. Survival and success of zirconia compared with titanium implants: a systematic review and meta-analysis. Clin Oral Investig. 2023;27(11):6279-90. Souza JGS, Nagay BE, Martins R, Bertolini M, Shibli JA, Aparicio C, et al. Engineered surface strategies to manage dental implant-related infections. Periodontol 2000. 2025;00:1-56. Rokaya D, Al Jaghsi A, Jagtap R, Srimaneepong V. Artificial intelligence in dentistry and dental biomaterials. Front Dent Med. 2024;5:1525505. Najeeb M, Islam S. Artificial intelligence (AI) in restorative dentistry: current trends and future prospects. BMC Oral Health. 2025;25:592. Sethumadhavan J, Siddiqui MF, Gholap P, Jadhav SM, Kadam NV, More S. Smart biomaterials shaping the future of dentistry: a comprehensive review. Cureus. 2026;18(1):e101904.